PENYULUHAN DAMPAK NEGATIF BERMAIN GAME DAN MENONTON TAYANGAN BERMUATAN KEKERASAN PADA ANAK (PENYULUHAN PADA SISWA SDN 2 RAJABASA, BANDAR LAMPUNG) - Oktiani, Hestin; Wardhani, Andy Corry; Ashaf, Abdul Firman; Suciska, Wulan (Prosiding Pengabdian FISIP Unila, 2012)
This community service was motivated by the condition in which there a lot of game and TV program containing violence consumed by children. In a city like Bandar Lampung, most parents do not have enough time to keep watching and accompany the children neither when playing the game nor watching TV. In addition, the children now have an easy access to play any game. The aim of this project is to deliver the knowledge to the children about the impact of violent contents in TVÂ  programÂ  and game. The method used inÂ  this activity was a talk show including showing the example of proper program for the children as well as the improper one, then it was comprehended by discussion session between the participants and the presenters. After this activity had been conducted,Â  the result showed that the average knowledge of the participants was in maximum value, 2 (after rounded up) which means there isÂ  47% increaseÂ  in the knowledge on the impact of violent contents in TVÂ  programÂ  and game. This result is expected to become aÂ  foundation for the participants to control the media they consumed without fully depending on parentsâ guidance and control.Â Â Key words: Media lite racy, media effect, violence, children